Pencegahan Penyakit Menular Melalui Pelatihan Cuci Tangan Pakai Sabun Pada Anak Sekolah Mi Muhammadiyah Singasari - Marta Tania Gabriel Ching Cing; Deisy Sri Hardini (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Clean and healthy living behavior is a form of health promotion effort so that family members to know, want and are able to play an active role in the health movement in society. Not only in adults, this behavior must also be instilled at the age of the child, so that they are accustomed to carrying out clean and healthy living habits for themselves. At school age children, they interact a lot with peers and do play activities as a learning process to develop cognitive, psychomotor and affective. They interact with people and devices that may be exposed to pathogenic bacteria or viruses. Washing hands with soap is one of the simplest activities to prevent transmission of these pathogens. By washing hands with good and correct soap, it is hoped that it can break the spread of viruses that land on / or stick to hands when handling objects before they touch other objects such as food or food. their own nose and mouth. Not only to prevent contagious infections, hygiene and healthy living habits washing hands is also done to prevent children from other diseases